Accessibility of automatic external defibrillators and survival rate of people with out-of-hospital cardiac arrest: A systematic review of real-world studies. (October 2021) - Ruan, Yihong; Sun, Gengqian; Li, Chaojuan; An, Yuanyuan; Yue, Lin; Zhu, Mengrong; Liu, Yuan; Zou, Kun; Chen, Dandi
Abstract: Objective: To evaluate the relationship between the accessibility of automatic external defibrillators (AEDs) and the survival rate of patients who have out-of-hospital cardiac arrest (OHCA). Methods: The systematic review was conducted according to the Cochrane Handbook of Systematic Reviews. We searched the Chinese and English literature databases from 2009 to 2019. Study selection and data collection were conducted by three reviewers. One-month survival rates of OHCA with different AEDs accessibility were estimated using meta-analysis. Results: Overall 16 studies with 55, 537 participants were included. The overall one-month survival rate for OHCA was 27.4%. The one-month survival rate was 35.2% for people receiving AEDs within 5 min, 36.6% between 5 min to 10 min, and 28.4% for longer than 10 min. By distance between the location of the AEDs and the location of the cardiac arrest, the one-month survival rate was 37.1% for those ≤100 m, 22.0% for 100 m-200 m, and 12.8% for >200 m, respectively. The one-month survival rate was 39.3% in schools, sports venues and airports compared with 23.5% in other sites. The number of AEDs allocation was positively correlated, while the time and distance were negatively correlated with the one-month survival rate adjusted for other factors, but they were all non-significant correlations. Conclusion: The improvement of accessibility of AEDs may increase the survival rate of OHCA and the survival rate may be higher in playgrounds, airports, and schools equipped with AEDs. However, the strength of evidence was limited by the considerably heterogeneity of included studies. Verification of these findings in further studies is warranted.